Long-term device survival and quality of life outcomes following artificial urinary sphincter placement - Boswell, Timothy C. (Transl Androl Urol, 2020)
BACKGROUND: Artificial urinary sphincter (AUS) placement is the standard for treatment of severe male stress urinary incontinence (SUI). While there is evidence to suggest satisfactory device survival, there is a paucity of data addressing long-term quality of life outcomes. METHODS: We identified patients who underwent primary AUS placement from 1983 to 2016. We assessed rates of secondary surgery (overall, device infection/erosion, urethral atrophy, malfunction) and factors associated with these endpoints. Quality of life was evaluated by pad usage and Patient Global Impression of Improvement (PGI-I) at various time points from primary surgery. Follow-up was obtained in clinic or by phoned/mailed correspondence. RESULTS: During the study time frame, 1,154 patients were eligible and included in the analysis. Patients had a median age of 70 years (IQR, 65–75 years) and median follow up of 5.4 years (IQR, 1.6–10.5 years). Overall device survival was 72% at 5 years, 56% at 10 years, 41% at 15 years, and 33% at 20 years. On univariate analysis, variables associated with need for secondary surgery were prior cryotherapy (HR 2.7; 95% CI, 1.6–4.6; P<0.01) or radiation therapy (HR 1.4; 95% CI, 1.1–1.7; P=0.01). On multivariable analysis, only cryotherapy remained significantly associated with this endpoint (HR 2.4; 95% CI, 1.3–4.2; P<0.01). While 36% and 23% of patients 5–10 years out from surgery and >10 years out from surgery, respectively, reported using a security pad or less per day, 78% and 81% of those patients, respectively, reported their PGI-I as at least “much better”. CONCLUSIONS: AUS placement has excellent long-term outcomes, and is associated with sustained improvement in patient quality of life.